2017
DOI: 10.1002/ece3.3577
|View full text |Cite
|
Sign up to set email alerts
|

Genetic substructure and admixture as important factors in linkage disequilibrium‐based estimation of effective number of breeders in recovering wildlife populations

Abstract: The number of effective breeders (N b) and effective population size (N e) are population parameters reflective of evolutionary potential, susceptibility to stochasticity, and viability. We have estimated these parameters using the linkage disequilibrium‐based approach with LDNE through the latest phase of population recovery of the brown bears (Ursus arctos) in Finland (1993–2010; N = 621). This phase of the recovery was recently documented to be associated with major changes in genetic composition. In partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…We begin with admixture, which can be pervasive in natural populations ( Hudjashov et al. 2017 ; Kopatz et al. 2017 ; Browning et al.…”
Section: Resultsmentioning
confidence: 99%
“…We begin with admixture, which can be pervasive in natural populations ( Hudjashov et al. 2017 ; Kopatz et al. 2017 ; Browning et al.…”
Section: Resultsmentioning
confidence: 99%
“…The degree of genetic differentiation observed among the Gobi and Himalayan populations is larger than the average Fst between distinctive subpopulations in northwestern Europe (0.051) [88]. Interestingly, the genetic differentiation between the southern (clade 1) and northern (clade 3a) subpopulations of Scandinavian brown bears has decreased from F ST = 0.051 to F ST = 0.014 during 20 years [89], because of an annual population increase of 4.5% and increased gene flow between these subpopulations [77, 90]. In contrast, a population genetic study [64] found a high pairwise F ST (0.23) between brown bear populations in the South Selkirk Mountains in North America, which has been isolated for several decades from the neighboring populations across a 5-km wide valley filled containing a town and rural farms.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, there are promising techniques using linkage disequilibrium to estimate effective population size (N e ). In recent examples, simulations demonstrated relatively accurate detection of early fragmentation into smaller units (England et al 2010), and the re-establishment of connectivity in a recovering system (Kopatz et al 2017). This method may not be well-suited to our study area because the populations of bears on each side of our studied fractures are rather large (see above).…”
Section: Discussionmentioning
confidence: 94%